Analisis tentang kinerja yang dipengaruhi oleh work environment dan work engagement dengan work motivation sebagai variabel intervening - Ali Imron Mashadi (FADZAT: Jurnal Ekonomi Syariah, 2022)
The aims of this study are: 1) To determine and analyze the effect of the work environment on work motivation. 2) To find out and analyze the effect of work engagement on work motivation. 3) To find out and analyze the work environment on performance. 4) To find out and analyze the effect of work engagement on performance. 5) To find out and analyze the effect of work motivation on performance. 6) To find out and analyze the work environment on performance with work motivation as an intervening variable. 7) To find out and analyze the effect of work engagement on performance with work motivation as an intervening variable. The population in this study were all employees in the Puri sub-district, Mojokerto Regency totaling 28 people. The sampling method in this writing uses the census technique. From the research results, it can be concluded as follows: 1) Work environment has no effect on work motivation. 2) Work engagement has a significant effect on work motivation. 3) Work environment has no significant effect on performance. 4) Work engagement has a significant effect on performance. 5) Work motivation has a significant effect on performance. 6) Work environment has an indirect effect on performance with work motivation as an intervening variable. 7) Work engagement has an indirect effect on performance with work motivation as an intervening variable.